A Sociotechnical Model of the Flight Crew Task. (December 2014) - Cahill, Joan; McDonald, Nick; Losa, Captain Gabriel
Objective: The objective of this research was to advance an improved model of Flight Crew task performance. Background: Existing task models present a "local" description of Flight Crew task performance. Method: Process mapping workshops, interviews, and observations were conducted with both pilots and flight operations personnel from five airlines, as part of the Human Integration into the Lifecycle of Aviation Systems (HILAS) project. Results: The functional logic of the process dictates Flight Crew task requirements and specific task workflows. The Flight Crew task involves managing different levels of operational and environmental complexity, associated with the particular flight context. In so doing, the Flight Crew act as a coordinating interface between different human agents involved in the Active Flight Operations process and other processes that interface with this process. Conclusion: This article presents a new sociotechnical model of the Flight Crew task. The proposed model reflects a shift from a local explanation of Flight Crew task activity to a broader process-centric explanation. In so doing, it illuminates the complex role of procedures in commercial operations. Application: The task model suggests specific requirements for pilot task support tools, procedures design, performance evaluation and crew resource management (CRM) training. Also, this model might be used to assess future operational concepts and associated technology requirements. Lastly, this model provides the basis for the operational validation of both existing and future cockpit technologies.